Integrating Halal Knowledge Towards Selection Of Islamic Banking Product: The Perspective Of Muslim Students - Mohamad Hafiz Rosli; Nur Fauzana Yahy; Hasnita Halim (USIM Press, 2024)
VOL. 28 NO. 1 Page (32-44)